862 Targeting PSGL-1, a novel macrophage checkpoint, repolarizes suppressive macrophages, induces an inflammatory tumor microenvironment, and suppresses tumor growth. (9th November 2020) - Nguyen, Phuong; Phennicie, Ryan; Kauffman, Kevin; Nowakowska, Dominika; Zafari, Mohammad; Komoroski, Veronica; Sazinsky, Steve; Wahle, Joe; Manfra, Denise; Vaidya, Shantashri; Brehm, Michael; Feldman, Igor; et al.
Abstract : Background: Macrophages play an important role in cancer by modulating both the innate and adaptive parts of the immune system. In non-pathological conditions, multiple subsets of macrophages balance the immune response. In cancer, M2-like immune-suppressive tumor-associated macrophages (TAMs) dominate the tumor microenvironment (TME). TAMs promote tumor growth, support neo-angiogenesis and enable metastasis formation. Macrophage modulators driving macrophage repolarization from the M2-like to a pro-inflammatory M1-like phenotype are an attractive novel class of cancer immunotherapy. Here we present identification, validation, and pre-clinical data of a novel macrophage checkpoint, PSGL-1, which supports targeting this molecule for immune-oncology. Methods: To assess the therapeutic potential of using anti-PSGL-1 antibodies to convert macrophage phenotype and the tumor microenvironment toward a more inflammatory state, we employed in vitro primary macrophage and multi-cellular assays, ex vivo patient-derived tumor cultures, and a humanized mouse PDX model. Results: Within the multiple subsets of macrophages, PSGL-1 is expressed at high levels on immune-suppressive TAMs and in vitro differentiated M2 macrophages. We show that targeting PSGL-1 via an antagonistic antibody repolarized M2 macrophages to a more M1-like state, both phenotypically and functionally as assessed in primary in vitro macrophage assays. Further, these repolarized M1-like macrophages enhanced the inflammatory response in complex multi-cellular assays, including SEB stimulated PBMC assays and mixed-lymphocyte reactions (MLRs). To establish a pre-clinical proof-of-concept for targeting PSGL-1, we turned to ex vivo cultures of fresh patient-derived primary tumors, where the complexity of the TME can be most preserved. RNA-seq data show that ex vivo cultures treated with anti-PD-1 antibody recapitulate TME changes in anti-PD-1 treated patients, including a strong T-cell IFN-gamma signature and a reduction in oncogenic pathway activation. Blocking PSGL-1 resulted in a robust pro-inflammatory signature driven by TNF-alpha/NF-kappa-B and chemokine-mediated signaling. The increase in TNF-alpha signaling was accompanied by reduction in oxidative phosphorylation and fatty acid metabolism. The increase in pro-inflammatory cytokine and chemokine production was confirmed by measuring secreted protein levels, further confirming the re-polarization of macrophages within a tumor setting. Lastly, we employed a humanized mouse PDX model of melanoma and show that anti-PSGL-1 treatment resulted in suppression of tumor growth favorably compared to anti-PD-1. At the cellular and molecular levels, anti-PSGL-1 treatment lead to a more enhanced inflammatory microenvironment, including a reduced M2:M1 macrophage ratio, increased antigen presentation, pro-inflammatory mediators, and effector T cell infiltration and activation. Conclusions: Our data support anti-PSGL-1 as a macrophage repolarizing agent and an effective macrophage-targeted therapy for Immuno-Oncology.